A gold elixir of youth in the 16th century French court. (16th December 2009) - Charlier, Philippe; Poupon, Joël; Huynh-Charlier, Isabelle; Saliège, Jean-François; Favier, Dominique; Keyser, Christine; Ludes, Bertrand
Abstract : Did gold play a part in the death of a 16th century French courtesan and favourite of Henri II?